2013
DOI: 10.1093/jpids/pit040
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Licensed Influenza A (H1N1) 2009 Monovalent Vaccines in HIV-Infected Children and Youth

Abstract: Background. With the emergence of pandemic influenza A ( pH1N1) in 2009, children and youth infected with human immunodeficiency virus (HIV) were vulnerable because of immunologic impairment and the greater virulence of this infection in young persons. Methods. A multicenter study of the immunogenicity of 3 licensed influenza A (H1N1) monovalent vaccines (1 live attenuated and 2 inactivated) was conducted in children and youth with perinatal HIV infection, most of whom were receiving 3 antiretroviral drugs, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Our analysis demonstrated a significant relationship between Hispanic ethnicity and higher antibody titers over time at nearly every time point of interest, including infection where the analysis approached significance ( p = 0.0624). Other groups have demonstrated higher rates of Hispanic SARS-CoV-2 seroconversion when compared to other ethnicities ( 39 , 40 ) and have found that Hispanic ethnicity is linked to higher rates of seroprotection and seroconversion following H1N1 monovalent vaccination ( 41 , 42 ), but future studies with a large number of participants are needed to support a generalizable trend for antibody magnitude over time in this population. Related, we also found that influenza vaccination was associated with higher antibody titers, though it was not significant following post-hoc testing.…”
Section: Discussionmentioning
confidence: 89%
“…Our analysis demonstrated a significant relationship between Hispanic ethnicity and higher antibody titers over time at nearly every time point of interest, including infection where the analysis approached significance ( p = 0.0624). Other groups have demonstrated higher rates of Hispanic SARS-CoV-2 seroconversion when compared to other ethnicities ( 39 , 40 ) and have found that Hispanic ethnicity is linked to higher rates of seroprotection and seroconversion following H1N1 monovalent vaccination ( 41 , 42 ), but future studies with a large number of participants are needed to support a generalizable trend for antibody magnitude over time in this population. Related, we also found that influenza vaccination was associated with higher antibody titers, though it was not significant following post-hoc testing.…”
Section: Discussionmentioning
confidence: 89%
“…Notably, our analysis demonstrated a significant relationship between ethnicity (Hispanic) and higher antibody titers over time at nearly every time point of interest, including infection where the analysis approached significance ( p = 0.0624). Other groups have demonstrated higher rates of Hispanic SARS-CoV-2 seroconversion when compared to other ethnicities [45, 46] and have found that Hispanic ethnicity is linked to higher rates of seroprotection and seroconversion following H1N1 monovalent vaccination [47, 48], but additional future studies with a large number of participants are needed to support a generalizable trend for antibody magnitude over time in this population.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, some studies demonstrated that the proportion of HIV-infected children generating a seroprotective response after influenza vaccination was as high as 79%. 8 …”
Section: Introductionmentioning
confidence: 99%